Influence of Motivation on Teachers’ Job Performance for Quality Assurance in Public Secondary Schools in North Central, Nigeria - , Moze, Eunice Terngu; Odeh, R.C.; Agbe, J.I. (IJRDO- Journal of Educational Research, 2019)
This study investigated the Influence of Motivation on Teachers’ Job Performance for Quality Assurance in Public Secondary Schools in North Central, Nigeria. The study sought to find out the influence of payment of regular salaries and provision of welfare packages on teachers’ Job Performance for Quality Assurance in Public Secondary Schools in North Central, Nigeria. Two research questions guided the study while two research hypotheses were tested at 0.05 level of significance. The study adopted survey research design. The population of the study was 6,560 teachers from 1,250 public secondary schools. Using Taro Yamen’s formula, the sample size of 377 teachers and 303 public secondary schools was selected. A 35 - item structured questionnaire developed by the researchers titled “Influence of Motivation on Teachers’ Job Performance for Quality Assurance Questionnaire (IMTJPQAQ)” was used as instrument for data collection. The questionnaire was validated by experts. The reliability coefficient obtained for the instrument was 0.68. Descriptive statistics of mean and standard deviation were used to answer the two research questions while Chi-square was used to test the two null hypotheses at 0.05 level of significance. The findings of the study revealed that payment of regular salaries and provision of welfare packages significantly influence teachers’ job performance for quality assurance in public secondary schools in North Central, Nigeria. Based on the findings of this study, the researchers recommended that adequate funds should be provided to pay teachers’ salaries and teachers’ welfare should be of paramount focus for higher productivity on the job.